A Qualitative Study of Social Construction in Boboiboy and Its Implications for Elementary Education - Fauziah, Siti Alfi; Baiquni, Achmad; Hamdani, Djaswidi Al; Rizal, Soni Samsu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Amidst the rapid currents of the postmodern era, children's media narratives no longer present a singular, black-and-white reality; rather, they are replete with fragmentation of meaning, moral ambiguity, and cultural hybridity. The animated series Boboiboy emerges as a popular culture artifact exercising strong dominance in constructing the imagination of children across the Nusantara region regarding the figure of the "hero." This study aims to deconstruct the concept of heroism depicted in Boboiboy and analyze its pedagogical implications for primary education. This research is a qualitative study grounded in the philosophy of science within the postpositivist paradigm. Data were collected through in-depth observation (thick description) of the audio-visual texts of the Boboiboy Galaxy series, and subsequently analyzed using hermeneutic approaches and critical discourse analysis. The research results reveal three fundamental findings Ontologically, Boboiboy deconstructs the singular subject into a fragmented subject (split subject) through the elemental split mechanism, reflecting a fluid and situational postmodern identity; Epistemologically, there is a shift in the validity of power from internal virtue (virtue ethics) toward technological determinism mediated by "power spheres."; Axiologically, the implications for primary education demand a transformation from a pedagogy of value transmission toward critical media literacy. Educators need to facilitate students in navigating the moral values behind technological simulacra, positioning popular culture as a space for critical dialectics within the classroom